Dairying in South Asian region: opportunities, challenges and way forward (SAARC Journal of Agriculture, 2017)
South Asian region is blessed with high diversity of dairy animal genetic resources. The role of dairying in livelihood, nutritional and food security of millions of people living in south Asian countries has been well understood. Among livestock, dairy animal assumes much significance since dairying is acknowledged as the major instrument in bringing about socio-economic transformation of rural poor and sustainable rural development. Dairying provides a stable, year-round income, which is an important economic incentive for the small holder farmers. Dairying directly enhance the household income by providing high value output from low value input besides acting as wealth for future investment. This region is home for about 745 Million of Dairy Animal Populations that accounts 21% of global daily animals. Besides, 25% of worlds cattle and buffaloes, 15% of the sheep and goat, and 7% of the camel are inhabitant in the region. South Asia is currently producing about 200 Million tons of milk that accounts around 20% of global production despite low productivity of the dairy animals. This study focused the data related to dairying in different countries of the region and situation analyses of input and delivery system for identifying the points of interventions to boosting dairy production and processing. In gist, this study documented the facts about the current dairying in the south Asia and envisages the priorities to make the dairying sustainable and more productive with the aim to cater the inclusive development of dairying in the region. It is hoped that this will provide a wealth of information to the researchers, planners, entrepreneurs and other stakeholders for upliftment of dairy industry in the region.SAARC J. Agri., 15(1): 173-187 (2017)